Gender Board Directors: Moderating the Effect of Green Accounting and Eco-Efficiency on Firm Value - Rabiyah Awaliyah; Budi Santoso; Siti Hidayati (International Journal of Management, Accounting and Economics)
The study aims to test whether gender has a moderating effect on green accounting and eco-efficiency on firm value. The population 90 companies were selected using purposive sampling technique, the research sample was 10 companies with a period of 5 years (2019-2023) so that the number of observations was 50. The results showed that green accounting had a negative and insignificant effect, eco-efficiency had a negative and insignificant effect on firm value, gender of the board of directors was able to moderate green accounting on firm value and was unable to moderate eco-efficiency on firm value. The implications of the research are expected to be taken into consideration by all property and real estate companies that the presence of women in the board of directors affects decision making in increasing company value, the results of this study include policy suggestions for policy makers so that in a company it is mandatory to have a woman in the board of directors because considering that there are no official regulations that require the involvement of women in the board of directors in property and real estate companies. The novelty of this research is to add the gender moderation variable of the board of directors.